Globalización, desarrollo sustentable y desarrollo económico - Da Costa, José Marcelino Monteiro (Revista EURE - Revista de Estudios Urbano Regionales, 1996)
This article intends to discuss aspects and matters about the trade off between the process of economic development and the concept. Still in formation, of sustainable development, having as a background the modern globalization of economy. The text is organized in six parts in which it can be read about the phenomenon of globalization and economic restructuration and its probable impacts on what concerns to structuration of new territorial configurations; about the identification of the stages of the evolution of the debate on environment; about the specific concept of sustainable development (S.D.) to be considered in the analysis; about the matters about practicability brought by the effective use of S.D.; and, finally, about conclusion.